2016
DOI: 10.52547/ethicnurs.5.2.5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between educational level and the Emergency Medical Services (EMS) staff quality of performance in dealing with cardiac arrest patients from the perspective of patients' rights

Abstract: Introduction:Providing health services with speed and high quality, especially for Urgent patients, is part of the Patients' Rights Charter. This study was conducted aiming at investigating the relationship between prehospital Emergency Medical Services staff Quality performance and their education when facing Cardiac Arrest patients. Materials and Methods:In this cross-sectional study, information about Educational level, Cardiopulmonary resuscitation measures in cardiac arrest patients and the number of hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Callanchan et al showed in a study that less than half (only 35%) of the patients with myocardial infarction who used pre-hospital emergency services in Dubai were fully satisfied (44). In addition, in a cross-sectional study by Jadidi et al, it was shown that patients' satisfaction or dissatisfaction with the quality of pre-hospital emergency services significantly affects their satisfaction with the overall services they receive from the healthcare system (45).…”
Section: Discussionmentioning
confidence: 99%
“…Callanchan et al showed in a study that less than half (only 35%) of the patients with myocardial infarction who used pre-hospital emergency services in Dubai were fully satisfied (44). In addition, in a cross-sectional study by Jadidi et al, it was shown that patients' satisfaction or dissatisfaction with the quality of pre-hospital emergency services significantly affects their satisfaction with the overall services they receive from the healthcare system (45).…”
Section: Discussionmentioning
confidence: 99%